(untitled) (KYAMC Journal, 2017)
We report a Bangladeshi family case of Hemoglobin E (Hb E) disorder. A 50 years old female and three of her family members had hemoglobin E disorder. Which was an incidental findings with nonspecific clinical problem and finally discovered the family pedigree of hemoglobin E disorder in asymptomatic other family members. Herein, we present the laboratory diagnosis and comparative data of the spectrum of Hb E disorders (i.e., heterozygous Hb E trait, homozygous Hb E disease) that was found in our index case and her offspring. Finally, genetic counseling & proper education gave to prevent the transmission of the abnormal gene in their progeny. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 653-655